Relationship between Individual Characteristics and Knowledge with Covid-19 Prevention in the Konda Health Center Area - Titi Saparina; Yustika Endah Rizky; Firmansyah; Mohamad Guntur Nangi (Miracle Journal of Public Health, 2022)
The development of Covid-19 in Indonesia based on reports from the Covid-19 Task Force as of January 10st 2021, amounted to 828.026 cases with the addition of daily cases of 9.640 cases. Meanwhile, there were 20 positive confirmed cases of Covid-19 at Konda Health Center, 18 suspected cases and 2 deaths. This study intends to examine the relationship between individual characteristics and knowledge with the prevention of Coronavirus Disease in the people of Konda District, South Konawe Regency. The research method is quantitative using a cross sectional study design. The research population was 21.196 people, with a sample of 96 people. The analysis method uses the Chi Square Test. The results showed that there was a relationship age with X2count = 26,808 > X2table = 3,841, there was a relationship sex with X2count = 25,011 > X2table = 3,841), there was a relationship education with X2count = 32,224 > X2table=3,841, there is a relationship knowledge with X2count = 26,709 > X2table= 3,841. The conclusion is that there is a relationship between age, gender, education, and knowledge with the prevention of Covid-19 in the community in the Konda Health Center area, South Konawe Regency. it is hoped that the Covid-19 team at the Konda Health Center, to be pro-active in carrying out counseling or outreach in providing Covid-19 education to the community, so that the community gets evenly distributed information which has an impact on increasing knowledge related to Covid-19 prevention.